Maré de resistência: a luta do movimento social ribeirinho diante da implantação portuária do agronegócio no Baixo Tocantins - SILVA, João Sérgio Neves da (Universidade Federal do Pará, 2022)
Traditional riverside communities in the region of the Abaetetuba islands will be affected by the construction and operation of the port complex of Cargill Agrícola S.A. Ways of life and survival are compromised and threatened by the intense navigation of barges in the Capim watershed. The new social movements are now not only mobilized and organized, in defense of their claims, but also in confrontation with their adversaries, and in the struggle for common rights. This study seeks to assess that riverine social movements are capable of producing political action strategies, in confrontation with the economic power of the company. he articulation of forces that, together with supporting institutions – Cáritas, CPT, STR, FASE, MORIVA, MP, Public Defender's Office of the State – offer a powerful form of organized resistance to the harmful effects of the economic interests of the company Cargill Agrícola SA The information was collected through a documentary survey and field research data, through qualitative methods, with interviews with the leaders of the local social movement, in total (08) and the leaders of the support institutions of six (06). Through a descriptive study of the action strategies and institutionalization mechanisms of the riverside social movement in Baixo Tocantins, it was revealed that the company makes their rights invisible as traditional populations in the territory, initiates a process of expropriation of populations, co-opts leaders, establishes its political and institutional connections with municipal, state and federal entities, for the construction of the TUP Abaetetuba port complex initiates the expropriation process, co-opts leaders, establishes political and institutional connections with municipal, state and federal entities, in order to complete the construction of the TUP Abaetetuba port complex.